2011
DOI: 10.1242/jeb.057836
|View full text |Cite
|
Sign up to set email alerts
|

Intra-retinal variation of opsin gene expression in the guppy (Poecilia reticulata)

Abstract: SUMMARYAlthough behavioural experiments demonstrate that colouration influences mate choice in many species, a complete understanding of this form of signalling requires information about colour vision in the species under investigation. The guppy (Poecilia reticulata) has become a model species for the study of colour-based sexual selection. To investigate the role of opsin gene duplication and divergence in the evolution of colour-based mate choice, we used in situ hybridization to determine where the guppy'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Thus, there may be further variation in l max among the four M/LWS loci, and there is a further possibility of allelic differentiation in the four loci related to l max because of amino acid variations other than the five sites as well as different expression patterns. The sensory variation could also be related to interindividual variation in the relative expression levels among opsin loci, as found in the Venezuelan guppies (Rennison et al, 2011). Direct measurements of l max for the reconstituted photopigments and quantification of the expression of the alleles are necessary to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there may be further variation in l max among the four M/LWS loci, and there is a further possibility of allelic differentiation in the four loci related to l max because of amino acid variations other than the five sites as well as different expression patterns. The sensory variation could also be related to interindividual variation in the relative expression levels among opsin loci, as found in the Venezuelan guppies (Rennison et al, 2011). Direct measurements of l max for the reconstituted photopigments and quantification of the expression of the alleles are necessary to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the amino acid that corresponds to residue 180 of the human M/LWS opsins that is known to affect l max , the LWS-1, LWS-2, LWS-3 and LWS-4 genes were originally designated as A180, P180, S180 and S180r, respectively. More recently, studies have demonstrated intraretinal variations and age/sex differences in opsin gene expression in guppies (Laver and Taylor, 2011;Rennison et al, 2011). Despite these advances, the genetic basis of interindividual sensory variation and the selection forces that maintain this variation remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The MSP data further suggests that some individuals may be expressing at least one different LWS as a double cone with peak absorption at 526/533 nm or as a twin cone with λ max of 553/553 nm but never both. At this point, we have no conclusive evidence suggesting that the LWS photopigments are either polymorphic or sex-linked (as in guppies [22], [52], [54], [72], [73], [74]), despite the extreme male color polymorphism. Our sample size is low and more in depth sampling across populations may perhaps reveal a sex-linked pattern of polymorphism.…”
Section: Discussionmentioning
confidence: 74%
“…Possible hexachromatic eyes would be composed of the following photoreceptors combinations (i) 355–407–456–526–533–543; and, (ii) 355–407–456–526–533–553. The choice of these two modeling approaches is based on our current knowledge of the differential expression of the SWS1, SWS2B, SWS2A, RH2 and LWS opsin subfamilies (often expressed in double cones) in Cyprinodontiformes, which suggests either a penta- or hexachromatic vision for these fishes (e.g., [50], [51], [52]). …”
Section: Methodsmentioning
confidence: 99%
“…Of note, LWS‐4 expression has only been reported in the peripheral‐dorsal retina of some individuals (Rennison et al. ), its role in guppy vision is currently unknown and it is the only Rh2 or LWS opsin that is found on a separate chromosome (e.g., Künstner et al. ; Watson et al.…”
Section: Resultsmentioning
confidence: 99%